Massive vulval edema with severe preeclampsia. Case report - Nelson Pérez Rumbaut; José Luis Durán Páez; José Luis Gómez Miranda (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Massive vulval edema with severe preeclampsia is presented as one of the consequences that may appear on patients with hypertension disorders during pregnancy, therefore the attention in the Obstetrics and Gynecology Service must be systematical and permanent. On women with hypertensive disorders during pregnancy, although edemas may not be constant, they may either appear at minor, barely perceptible extents, or even in the most severe ways, such as anasarca. A very peculiar manifestation of edema on preeclampsia is massive vulval edema, which appears as a highly rare complication, in whose basis there is a complex, systemic pathological process involved. We present a case of a pregnant woman who was admitted with high blood pressure values and excessive weight gain, plus very noticeable general edemas, and during her stay developed massive vulval edema. No data on this complication were found in the bibliography reviewed. Very few experienced professionals recall having dealt with similar cases in the last fifteen years, hence the decision to publish it.